EFFECTS OF TEACHING METHODOLOGIES ON ENGLISH LANGUAGE SKILLS AT SECONDARY LEVEL IN MULTAN - Dr. Abdul Waheed Qureshi; Huda Hameed Qureshi; Samreen Riaz Ahmed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
English is taken as the international medium of communication. It is learned at all stages in Pakistan. In southern Punjab, District Multan is the most developed city. National as well as international curricula are taught in institutes to enhance linguistics competence. It can be observed that many English medium institutions are being established to promote linguistic competence. This statistic study shows that in Multan, the teachers of English do a great deal in developing linguistic competence enhancement of students of District Multan. The study reveals that the contents and the methodologies which are used while enhancing linguistic competence need to be reviewed. Teachers still use old methodologies which are only helpful in enhancing writing and reading skills. It requires the new trends in evaluation system and inclusion of speaking and listening contents in English language curriculum which will further require CLT and Direct Method to enhance language skills.